Direct Recycling of Rubber: Effect of Staged Mixing on Bulk and Surface Properties of Thermoplastic Macro-Composites - Rakhman, Moshe Z (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The novel concept was used to upcycle GTR via cleavage of a cross-linked network with subsequent conversion into macro-composite. The pre-blend, which comprised loose 74 wt% GTR, was compacted with the matrix fusing under ram pressure. The final master step ensured the better bulk properties (interfacial adhesion, removal of macro-voids, viscosity) and the regular surface of the D2 blend, comprised of 20 phr SEBS. The extent of fragmentation could not be directly appraised, where traditional testing had failed to identify them. The regular surface quality and reduced viscosity of blend D2 evidence the decrease in size particles, accompanied by improving bulk properties (interfacial adhesion, removal of macro voids). The interactions were quantified using an analysis of peel strength; elastic recovery, tear, and tensile strength. Direct reprocessing via two-staged mixing governed the conversion of GTR to thermoplastic macro-composite., excluding the reclaim step.